2008
DOI: 10.1080/14653240802075476
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter comparison study between the Endosafe® PTS™ rapid-release testing system and traditional methods for detecting endotoxin in cell-therapy products

Abstract: Background-Rapid release testing reduces the waiting period for administration of time-sensitive cell therapy products. Current assay systems are labor intensive and time consuming. The Endosafe ® Portable Test System (PTS™) is a chromogenic Limulus Amebocyte Lysate (LAL) portable endotoxin detection system which provides quantitative results in approximately 15 minutes. To evaluate Endosafe ® performance, specifically with cell therapy products, side-by-side testing of traditional LAL systems, and the Endosaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 2 publications
2
40
0
Order By: Relevance
“…Furthermore, according to the manufacturer, the rapid endotoxin test requires laboratory equipment, which negates the aim of having a method that could be rapidly used to measure microbial load in the field. In accordance with our study Gee et al (2008) found no significant difference between traditional and rapid LAL test regarding endotoxin activity of 178 samples from cell therapy products However, they pointed out as well that it is a major limitation of the test that only one dilution at a time is measurable. In conclusion based on our study, it is not reasonable to suggest the rapid test Endosafe for the analysis of humidifier water directly in the field.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, according to the manufacturer, the rapid endotoxin test requires laboratory equipment, which negates the aim of having a method that could be rapidly used to measure microbial load in the field. In accordance with our study Gee et al (2008) found no significant difference between traditional and rapid LAL test regarding endotoxin activity of 178 samples from cell therapy products However, they pointed out as well that it is a major limitation of the test that only one dilution at a time is measurable. In conclusion based on our study, it is not reasonable to suggest the rapid test Endosafe for the analysis of humidifier water directly in the field.…”
Section: Discussionsupporting
confidence: 91%
“…Methods without culturing are for example DNA sequencing (Nonnenmann et al, 2010), fluorescence analysis using DAPI staining (Klug and Jäckel, 2012), measurement of endotoxin activity with the LAL test (Gee et al, 2008;Liebers et al, 2009), detection of pyrogenic activity with whole blood assay (Liebers et al, 2010;Punsmann et al, 2013), determination of fungi antigen or ␤-glucan by the ELISA technique (Sander et al, 2008(Sander et al, , 2012Zahradnik et al, 2013), and ATP content via bioluminescence (Hammes et al, 2010;Mueller et al, 2009;Liebers et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…A recombinant Bet (based on a genetically engineered protein from the Carcinoscorpius clotting cascade), which does not consume any animals, has been developed and validated to some extent (Ding and Ho, 2001;loverock et al, 2010). Special lAl-techniques have been developed for testing very small sample volumes (Jimenez et al, 2010;Gee et al, 2008).…”
Section: In Mononuclear Cells When the 4/2 Acyl Chain Pattern Of Entementioning
confidence: 99%
“…The problem with this test is not the time (results can be usually obtained in 3-4 hours), but its sensitivity to external factors and complexity of its setting. Endosafe® PTSTM is a chromogenic LAL test that provides quantitative results in approximately 15 minutes (Gee et al, 2008). It has been already validated for testing of bone marrow mononuclear cells for cardiac regeneration (Soncin et al, 2009), and is relatively easy to use.…”
Section: Endotoxin Testingmentioning
confidence: 99%